Grow Up, Level Up, and Game On; Evolving Games Research - Kneer, Julia (2018)
Playing host to articles written in different disciplines and perspectives on the shared subject of digital gaming, the current special issue means to galvanise interest in and recognition of the nascent field of games research. Despite being little more than 50 years old, the medium of digital games has seen a meteoric rise to economic and cultural prominence across the globe. A cultural shift accepting games as a worthwhile recreational activity (and more) is likewise resulting in shifting attentions within game studies. Games were seen as frivolous and even harmful, and research traditionally focused on the negative effects they were perceived to have while in the end coming up with very little reliable evidence to support this position. The current wave of games research exemplified in this issue is certainly wider: games are a cultural and often highly socialised medium that has changed the way we view the world. They are used in non-entertainment settings, helping to promote active learning in players of all ages. The medium also facilitates deeper psychological and philosophical theorizing, as researchers grapple with deeper questions on what games and play mean to each of us. Put simply: games research is not just fun and games.